Indonesian Flipbook-Based Educational Magazine with Regional Decorations for Fifth Grade Elementary School - Yani, Candrika Deva; Setiawan, Deni (Jurnal Pedagogi dan Pembelajaran, 2024)
This research is motivated by learning problems, especially in terms of students' knowledge of regional decorative materials. This problem occurs due to students' lack of understanding of regional decorative material, causing student learning outcomes to not reach the KKM. This research aims to develop flipbook-based educational magazine media containing Indonesian language in improving student learning outcomes on regional decoration material for fifth grade elementary school students. The method used in this research is research and development research using the Borg and Gall development model. Product validity testing is carried out with material expert validators and media expert validators. The research results showed that the results of the media feasibility test were 86% with the predicate "very feasible", and the results of the feasibility test from material experts were 88% with the predicate "very feasible". The results of the effectiveness test from the trial use can be seen from the results of the pretest and posttest on a large scale. In the effectiveness test of the pretest and posttest, there was an increase in student learning outcomes after using Indonesian educational magazine media with regional decoration material. The conclusion from the research results based on development, feasibility testing with media validation, and effectiveness testing with pretest and posttest shows that there is an increase in learning outcomes in understanding regional decorative material in fifth grade students.